The palliative care experiences of adults living in regional and remote areas of Australia: A literature review. Issue 1 (2nd January 2017) - Jansson, Melissa; Dixon, Kathleen; Hatcher, Deborah
Abstract : Background: Regional and remote areas are often disadvantaged in terms of access to palliative care services. The impact of reduced access to services on people living in regional or remote areas of Australia is poorly understood. Objective: Identify and examine current literature relating to the palliative care experiences of adults living in regional and remote areas of Australia. Methods: CINAHL, Medline, PubMed, Cochrane Review Library and grey literature were searched using a combination of keywords. A thematic analysis was applied. Results: Thirteen articles were included in the final review. Poor access, relocation and hardship were identified as issues affecting participants. Conclusion: Limited literature was available addressing the palliative care experiences of adults living in regional and remote areas of Australia. To identify and address any inequities in palliative care provision and access, the experiences of palliative care patients living outside major cities need to be examined.